2001
DOI: 10.1097/00004714-200104000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Response to Open-Label Venlafaxine in Drug-Resistant Major Depression

Abstract: The aim of this study was to evaluate the response to venlafaxine in patients with treatment-resistant depression during an extension phase of an open-label study of venlafaxine. After completing the initial 8 weeks of the study, patients could continue venlafaxine treatment for an additional period of up to 10 months. Efficacy results are given for 149 patients with treatment-resistant depression. Response was defined as a 50% reduction in scores on the Montgomery-Asberg Depression Rating Scale (MADRS); 69% w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2001
2001
2007
2007

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 9 publications
1
17
0
1
Order By: Relevance
“…This study aimed to examine remission based on a categorical MADRS score less than ten. Other studies have used MADRS scores ranging from less than 9 to less than 12 to define remission (Forlenza et al, 2001;Schweitzer et al, 2001). Thus, the cut-off of less than 10 in the present study seems reasonable.…”
Section: Discussionmentioning
confidence: 75%
“…This study aimed to examine remission based on a categorical MADRS score less than ten. Other studies have used MADRS scores ranging from less than 9 to less than 12 to define remission (Forlenza et al, 2001;Schweitzer et al, 2001). Thus, the cut-off of less than 10 in the present study seems reasonable.…”
Section: Discussionmentioning
confidence: 75%
“…Open-label studies of venlafaxine for TRD have typically shown a response in approximately half of patients [De Montigny et al, 1999;Kaplan, 2002;Schweitzer et al, 2001]. In one randomized, double-blind trial of venlafaxine for TRD, the reported response rate [Z50% decrease from baseline in the 17-item Hamilton Depression Rating Scale and Clinical Global Impression (CGI) Improvement score of 1 or 2] was 45%, and the remission rate (Hamilton Depression Rating Scale score o10 on day 28) was 37% [Poirier and Boyer, 1999].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that SSRIs and SNRIs are effective for MDD when patients remain on therapy at the minimum recommended dose and duration of time set forth in clinical practice guidelines (at least 4-9 continuous months). [18][19][20] Although many antidepressants have similar efficacy as first-line agents, few studies have compared them as second-line treatments following initial treatment failure. 21 …”
Section: Nn Treatment Optionsmentioning
confidence: 99%
“…33 nn Managed Care Strategies to Improve Depression Treatment Outcomes When depressed patients maintain continuous therapy for the recommended treatment duration, health care resource costs are reduced compared with patients who discontinue therapy early. 20,34 It then follows that overall costs should decrease when patient compliance is improved and agents associated with a reduced incidence of early discontinuation and therapy change are utilized early in the treatment program. 35 Managed care organizations (MCOs) are challenged to identify optimal, cost-effective strategies for the treatment of depression and improve patient adherence to antidepressant therapy.…”
Section: Treatment-resistant Depressionmentioning
confidence: 99%
See 1 more Smart Citation